Based on Role Expectation to Discuss Role Ambiguity and Practice of University Teachers in Business Administration - Deng, Yun; Zeng, Haimei; Xu, Anxin; Chen, Youcheng (Frontiers in Psychology, 2022)
As a result of social change, the issues such as complexity of family structure, and increasing student problems are becoming more complicated. Both schools and parents have high expectations of teachers, and expect them to solve the problems. Considering the many different factors involved in this issue, this could lead to a psychological and physiological imbalance in teachers, especially in relation to their emotions which results in role ambiguity. The participants of this study consisted of teachers in business administration departments of universities in China. During data collection, 450 copies of the questionnaire were distributed. A total of 363 valid copies were retrieved, with a retrieval rate of 81%. It can be concluded that the results of this study can help national university faculty present professional spirit and attitude towards the professional service, which in turn promotes the standard of national education in universities.